Economic Valuation of Health Impact of Tightening and Easing PSBB Policies in DKI Jakarta - Dewanto, Alfalast Susetyo; Halimatussadiah, Alin (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2022)
Coronavirus Disease 2019 or COVID-19 is a pandemic that has affected more than 200 countries around the world. This study aims to see the benefits of differences in the policy of easing the lockdown or PSBB (Pembatasan Sosial Berskala Besar), and in the progressive tightening of PSBB execution that had taken place from early March until 31 August 2020. The health impact benefits are calculated using the morbidity which includes Medical Costs and Temporary Productivity Loss (TPL), and the mortality which includes the Value of Statistical Life (VSL). ARIMA model is used for prediction simulation on positive cases of COVID-19 and benefit-transfer method for predicting death cases. If the strict rules are saliently successful in containing the development of positive cases, then DKI Jakarta will only have 54.2% or 18,460 cases and the death will only be 550 cases. Benefits of medical costs that can be incurred could save the health budget amounting to IDR1.26trillion. TPL affects most of those aged between 25–29, 30–34, and over 60 years and it also yields a benefit of IDR56 billion. From the death of many people aged over 60 years, it will contribute to the benefits of VSL amounting to IDR15.5 trillion.